Dynamic type water filtering system for indigenous people - Mohd Hudzari, Haji Razali; Abd Jamil, Zakaria; Noordin Asimi, Mohd Noor; Hasbullah, Muhammad (2014)
This study is focused towards the removal of dirt that causes clogging on filtering system at highland irrigation especially for Islamic community of indigenous people. The site study was at Kampung Sungai Bot, Bt.8, Jalan Pahang, Tapah, Perak, Malaysia. Residents in rural areas especially in highland area need clean water sources for agricultural and consumer use. However, topography and weather conditions often cause the quality of natural water resources become less favourable while the open reservoir system can cause debris collection from the environment that will be the cause of a clogged water filter. Their rural area at remote site makes it difficult to get clean water and electricity resources. In this study, the combination of using stainless steel and dynamic shape of body structure with increasing the total surface of area index while non-require any power source for operating this filter system shows it novelty. These filtering systems are contained fine-hole netting system, chain-locked security and flexible fixture that were assemble on existing inlet point of highland reservoir. Fine-hole netting system is used for prevention that only the clean water can pass through the filter and then flow on long hill piping system before stuff into consumer home tank house. The designed filter is shaped deliberately for debris that stick on surface due filtered operation, will dynamically flow out at outlet point on wall of hill reservoir. Maximum use of natural resources such as hills water resources can be reduce of management costs and protect the environment from pollution. The result from this study is producing a prototype containing filter for highland irrigation. Indigenous people will no more always to claim up the hill for cleaning their water filter especially during just after raining and now, they only maintained the water filter, once per six month compare on every month as well. Even the consumer can get clean water, in fact for Muslim can continuously done on their ablution for praying on his daily Islamic practise.